(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
A stratigraphic unit, Early Aptian in age, equivalent to the Lower Aptian Livello Selli of the Umbria-Marche Basin, has been recognized in the Lombardy Basin (Southern Alps) and is here described. The unit is up to 3 m thick, and consists of alternating pelagic calcilutites, marlstones, black shales and rare pelagic turbidites. Due to the uneven basin morphology, with intrabasinal structural highs, the Livello Selli Equivalent unit (LSE) is often lacking. The LSE is located in the central part of a stratigraphic unit, locally bounded by discontinuities, that is here interpreted as a complete transgressive/regressive (T/R) cycle of latest Barremian to Late Aptian age. The sedimentary features of this cycle, can be used to support comparisons between the lombardian succession and those from other basins.